In the problem of setting engineering geomorphological suitability criteria for urban and settlement zone: Хот, суурин газрын суурьшлын бүсийн инженер геоморфологийн тохиромжтой байдлын шалгуур үзүүлэлт боловсруулах асуудалд - Altanbold, Enkhbold; Ulambadrakh, Khukhuudei; Amarbat, Galsantsevel; Gansukh, Yadamsuren; Byambakhuu, Gantumur; Khishigdorj, Batzul (Geographical Issues, 2023)
In Mongolia, engineering geological study is developed as much when constructing urban settlement areas, but engineering geomorphological concerns have been not used in practice. In this study, we focused on the aufeis formation to influence to urban and land planning, a part of engineering geomorphological study. Our results of study are occurred by relevant methods, and based on geomorphological, geological, tectonic, hydrogeological, and engineering-geological base maps of the Eg River valley. According to our results, near of Erdenebulgan soum has consistent by geomorphological and tectonic indicators and non-consistent by geological, hydrogeological, engineering geological and permafrost indicators. Correlation between aufeis square, volume and precipitation is in average r=0.60, r²=0.35 and p=0.05. This result shows that 35% of aufeis square and volume is related to precipitation, and 65% is likely related to other geo-spatial conditions. We concluded that in the next step engineering geomorphological indicators would include necessarily in the land and settlement planning, and waste management of Erdenebulgan soum. In the future, following this criterion, it will eventually be feasible to test, compare, and ascertain the engineering geomorphological conditions in different study areas.